2018
DOI: 10.1103/physrevlett.120.043204
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Ultraviolet Frequency Metrology of H2 for Tests of Molecular Quantum Theory

Abstract: Molecular hydrogen and its isotopic and ionic species are benchmark systems for testing quantum chemical theory. Advances in molecular energy structure calculations enable the experimental verification of quantum electrodynamics and potentially a determination of the proton charge radius from H_{2} spectroscopy. We measure the ground state energy in ortho-H_{2} relative to the first electronically excited state by Ramsey-comb laser spectroscopy on the EF^{1}Σ_{g}^{+}-X^{1}Σ_{g}^{+}(0,0) Q1 transition. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 53 publications
(79 reference statements)
5
86
0
Order By: Relevance
“…Similarly to direct frequency comb spectroscopy, the free spectral is limited to the comb repetition frequency frep, so that the technique is mostly suitable for metrology of simple spectra with few transitions. As already demonstrated in the deep ultraviolet with two--photon transitions of H2 ( Fig.5b) around 202 nm (1,485 THz) 52 , Ramsey--comb spectroscopy holds particular promise, because the pairs of phase--coherent infrared pulses amplified to the millijoule level allow efficient frequency conversion. 3.3 Spectroscopy using a dispersive spectrometer Dispersive spectrographs ( Fig.3c) provide simple and robust tools for multichannel approaches to broadband spectroscopy with frequency combs.…”
Section: Ramsey--comb Spectroscopymentioning
confidence: 79%
“…Similarly to direct frequency comb spectroscopy, the free spectral is limited to the comb repetition frequency frep, so that the technique is mostly suitable for metrology of simple spectra with few transitions. As already demonstrated in the deep ultraviolet with two--photon transitions of H2 ( Fig.5b) around 202 nm (1,485 THz) 52 , Ramsey--comb spectroscopy holds particular promise, because the pairs of phase--coherent infrared pulses amplified to the millijoule level allow efficient frequency conversion. 3.3 Spectroscopy using a dispersive spectrometer Dispersive spectrographs ( Fig.3c) provide simple and robust tools for multichannel approaches to broadband spectroscopy with frequency combs.…”
Section: Ramsey--comb Spectroscopymentioning
confidence: 79%
“…The hydrogen molecule exhibits an electronic structure with a series of characteristic double-well potential energy curves. The lowest of those in the manifold of gerade symmetry, the EF 1 + g state, was identified by Davidson [1] and subsequently investigated by laser spectroscopy at ever increasing precision [2][3][4][5][6][7][8][9][10]. The next double-well state of g-symmetry, the GK 1 + g state was identified initially in the study by Wolniewicz and Dressler [11] and later investigated theoretically by Yu and Dressler [12] and Ross and Jungen [13].…”
Section: Introductionmentioning
confidence: 99%
“…So far only very fragmentary high-accuracy spectroscopic data are available on electronically excited states of these molecules. In the case of H 2 , Altmann et al 17 have measured the interval between the X 1 Σ + g (v = 0, N = 1) ground state and the EF 1 Σ + g (v = 0, N = 1) excited state at an accuracy of 73 kHz (∆ν/ν = 2.4 × 10 −11 ). Beyer et al 18 have reported the interval between the GK 1 Σ + g (v = 0, N = 2) and high Rydberg states at an accuracy of 64 kHz (∆ν/ν = 1.7 × 10 −10 ).…”
Section: Introductionmentioning
confidence: 99%